Real-life quantitative G6PD screening in Plasmodium vivax patients in the Brazilian Amazon: A cost-effectiveness analysis. - Jose Diego Brito-Sousa; Henry M Peixoto; Angela Devine; Alexandre V Silva-Neto; Patricia C S Balieiro; Vanderson S Sampaio; Sheila Vitor-Silva; Maxwell O Mendes; Brenda K A Souza; Marcus V G Lacerda; Wuelton M Monteiro (Public Library of Science (PLoS), 2022)
Background As quantitative glucose 6-phosphate dehydrogenase deficiency (G6PDd) screening tools are evaluated in operational studies, questions remain as to whether they are cost-effective. Here, a cost-effectiveness analysis (CEA) was performed to estimate the Incremental Cost-effectiveness Ratio (ICER) of the introduction of quantitative screening test to detect G6PDd among P. vivax carriers in two municipalities in the Brazilian Amazon. Methodology/principal findings This cost-effectiveness analysis evaluated the use of the Standard G6PD quantitative screening test in vivax malaria treatment units in two municipalities of the Brazilian Amazon. Using the perspective of the Brazilian public health system, the analysis was performed for the outcome 'PQ-associated hospitalization avoided', based on a decision tree model. The results indicated that the G6PDd screening strategy compared with the routine strategy was highly cost-effective, with an ICER of US$495 per additional hospitalization avoided, which represented less than 8% of one Brazilian gross domestic product per capita (US$6,822). The uncertainties evaluated in the sensitivity analysis did not significantly affect the ICER identified in the base-case. Conclusions/significance This cost-effectiveness analysis showed the quantitative G6PD testing was effective in avoiding PQ-associated hospitalizations. The incorporation of G6PD screening is of paramount importance towards P. vivax malaria elimination in the Amazon to promote the safe use of primaquine and tafenoquine.